Photophysiological Tolerance and Thermal Plasticity of Genetically Different Symbiodiniaceae Endosymbiont Species of Cnidaria - Russnak, Vanessa; Rodriguez-Lanetty, Mauricio; Karsten, Ulf (Frontiers in Marine Science, 2021)
Coral reefs are endangered by constantly rising water temperature due to global warming. This triggers a breakdown of the nutritional symbiosis between cnidarian hosts and their Symbiodiniaceae symbionts, resulting in the loss of the algal partner. In the Symbiodiniaceae exists a high genetic diversity with broad physiological plasticity within and between species, resulting in large thermal tolerance. While these variations have been studied in individual taxa, comprehensive comparative experimental data on numerous species are still rare. In the present study, the photosynthetic performance and tolerance as function of light and temperature of nine Symbiodiniaceae genetic types of four different clades were determined. The data indicate significant differences in the response patterns. Almost all algal isolates exhibited low to moderate light requirements for photosynthesis without photoinhibition, and a photosynthetic efficiency between 20% and 80% in the temperature range 20°C-34°C, indicating a broad thermal tolerance to temperature fluctuations in tropical regions. The presented data clearly point to a broad photophysiological tolerance and thermal plasticity of genetically different Symbiodiniaceae, this contributes as an important finding to a better understanding of host-symbiont response to an increasing sea surface temperature.